2008
DOI: 10.1111/j.1939-1676.2008.00124.x
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug‐Resistant E. coli and Enterobacter Extraintestinal Infection in 37 Dogs

Abstract: Background: Extraintestinal infections caused by multidrug-resistant (MDR) Escherichia coli and Enterobacter are becoming more common in veterinary medicine.Objective Methods: Retrospective case series assembled from hospital records data, including clinical history before 1st MDR isolation and treatment outcome. Identity and antimicrobial susceptibility profiles were confirmed by standard microbiological techniques for 57 isolates.Results: Most dogs had an underlying disease condition (97%), received prior an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 23 publications
(54 reference statements)
1
56
1
3
Order By: Relevance
“…Antimicrobial resistance in E. coli is of concern in this tropical island, except for imipenem, which is a last-resort drug for multidrug-resistant E. coli. 16 Over 40% of the E. coli isolates in this study showed multiple drug resistance to 2 to 6 classes of drugs, and one isolate was resistant to cefotaxime, which indicates resistance to extended spectrum cephalosporins. 7 This is of concern in small animal medicine as well as of public health significance when the genes are transferable.…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial resistance in E. coli is of concern in this tropical island, except for imipenem, which is a last-resort drug for multidrug-resistant E. coli. 16 Over 40% of the E. coli isolates in this study showed multiple drug resistance to 2 to 6 classes of drugs, and one isolate was resistant to cefotaxime, which indicates resistance to extended spectrum cephalosporins. 7 This is of concern in small animal medicine as well as of public health significance when the genes are transferable.…”
Section: Discussionmentioning
confidence: 99%
“…TCC may cause a failure of host barriers as a result of abnormal patterns of voiding, decreased mucosal defenses caused by changes in the uroepithelium, and by decreased antibacterial properties caused by alterations of urine pH or host defense peptides, thereby predisposing to UTI 8, 9, 10, 11, 12. Previously, published studies have shown that underlying illness contributing to immunosuppression is a risk factor for development of persistent or recurrent infections, suggesting that patients with cancer, those receiving chemotherapy or both may be at higher risk of UTI 10, 13, 14. Possible sequelae to untreated bacterial UTI include renal failure, pyelonephritis, lower urinary tract dysfunction, septicemia, prostatitis, discospondylitis, or anemia 8, 9, 10, 11, 15, 16…”
mentioning
confidence: 99%
“…Thirty percent of isolates, 54% of which were E. coli, were classified as MDR, which is not surprising given that prior exposure to antimicrobials is a recognised risk factor for multidrug-resistance (Gibson et al, 2008;Hernandez et al, 2014). Twelve dogs in this study did not have MDR isolates on initial presentation but subsequently had MDR isolates cultured.…”
Section: Coli K Pneumoniae Staphylococcus Pseudintermedius Enteromentioning
confidence: 84%
“…A change in the predominant MDR E. coli resistance profile in an Australian veterinary teaching hospital over time (1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006) has also been documented (Gibson et al, 2008). Profiles prevalent in later years, although similar to the prevailing early profile, changed in susceptibility to 3 rd generation cephalosporins and cefoxitin (Gibson et al, 2008). More recently, a study conducted on positive canine urine cultures in the United Kingdom documented increasing multiple antimicrobial resistance for P. aeruginosa and E.…”
Section: Observations Of Increasing Antimicrobial Resistance In Caninmentioning
confidence: 99%
See 1 more Smart Citation